2009
DOI: 10.1111/j.1600-0781.2009.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Broadband targeted UVB phototherapy for localized vitiligo: a retrospective study

Abstract: Phototherapy with ultraviolet B (UVB) or PUVA has been used in the treatment of vitiligo for many years. The aim of this study was to analyze retrospectively the efficacy and safety of targeted broadband UVB phototherapy in patients with localized vitiligo. Thirty-two patients (14 male, 18 female), aged 18-65 years, were treated with Daavlin T500x High Dose Targeted Phototherapy System. Patients were treated twice or thrice weekly, totaling 20 to 60 sessions. Out of 32 total patients, only four patients (12.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…These devices include 'BClear' that delivers broadband UVB, 'Multiclear' or 'Dualight' providing UVA and UVB combination and lastly 'Bioskin' which gives a NBUVB waveband peaking at 311nm [14][15][16]. Clinical studies have demonstrated that the results obtained are similar with the BB-UVB and NBUVB Targeted phototherapy devices in vitiligo [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These devices include 'BClear' that delivers broadband UVB, 'Multiclear' or 'Dualight' providing UVA and UVB combination and lastly 'Bioskin' which gives a NBUVB waveband peaking at 311nm [14][15][16]. Clinical studies have demonstrated that the results obtained are similar with the BB-UVB and NBUVB Targeted phototherapy devices in vitiligo [17].…”
Section: Discussionmentioning
confidence: 99%
“…Targeted UV light-based therapies employ conventional noncoherent ultraviolet light that is delivered through fibre-optic cable systems specifically to the treatment area. These machines deliver the light energy in seconds and have larger spot sizes [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with microphototherapy can cause various tolerable adverse effects including erythema, blistering, hyperpigmentation, erosion, burning, and itching (3,6,(16)(17)(18). Therefore, in the present study the patients were asked about the occurrence of any of these side effects.…”
Section: Discussionmentioning
confidence: 99%
“…They reported repigmentation from a comparison of baseline photographs with those after 30 sessions by two independent investigators and they concluded that UVB microphototherapy seemed to be effective for the repigmentation of vitiligo in lesions located on the face instead of acral lesions. Akar et al 8 declared that despite the fact that the safety of targeted broadband UVB phototherapy in the treatment of localized vitiligo was good, its therapeutic effectiveness was limited and depended on the location of vitiligo lesions. To increase the efficacy, microphototherapy can be combined with other therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Microphototherapy can cause various tolerable adverse effects including erythema, blistering, hyperpigmentation, erosion, burning and itching 8,[13][14][15][16] . Therefore, in this study, the patients were observed for the occurence of any of these side effects.…”
mentioning
confidence: 99%